Perilaku Makan Ibu Menyusui dengan Status Gizi Bayi 0-6 Bulan - Ratna Zahara; Tabitha Javingkan Siregar (Journal of Telenursing (JOTING), 2022)
This study aims to determine the relationship between the eating behavior of breastfeeding mothers and the nutritional status of infants 0-6 months in Central Helvetia. The method used is an analytical survey with a cross-sectional design. Sampling was done by simple random sampling method. The statistical test used for data analysis is the chi-square test. The results showed that the nutritional status of infants with a weight/age index was more in the normal category, namely 87.8%, and mothers with good eating habits were 32 respondents (78.0%). In conclusion, there is a significant relationship between the eating behavior of breastfeeding mothers and the nutritional status of infants 0-6 months. Keywords: Eating Behavior of Breastfeeding Mothers, Nutritional Status of Infants